Integral utilization of mango pulp residue in the preparation and sensory evaluation of fermented milk (Research, Society and Development, 2020)
Mango (Mangifer indica L.) is a tropical fruit much appreciated for its sensory characteristics, however, it is an extremely perishable food, and part of its production is destined to the product processing industry. In this processing tons of waste are produced, which are rich in many nutrients, but most of them are discarded, becoming an environmental contaminant. One way around this problem is to make full use of these components that can be added to traditionally consumed products such as yogurt. Thus, the objective was to elaborate different formulations of yogurt added to mango residue flour, as well as to evaluate the sensory characteristics of the elaborated products. Initially, the mango residues were dried in an air circulation oven at 60 ° C / 24 hours and then the flour was prepared. Subsequently, different yogurt formulations were made: IC (0% of mango residue flour), IM5% (0.5% of mango residue flour) and IM10% (1.0% of mango residue flour) . Sensory analysis was performed through acceptance test using the 9-point hedonic scale and purchase intention test. Based on the results, it can be observed that the CI had an acceptability higher than 80% for all the evaluated attributes, while the IM5% sample showed an acceptability index higher than 74% and the IM10% had an acceptability index above 62% for all attributes. the attributes appreciated. In this context, it was found that, sensorially, the IM5% presented good acceptance, proving to be a viable alternative to add nutritional value to yogurt.